Patterns of rapid weight loss in elite sambo athletes - Patrik Drid; Flavia Figlioli; Nemanja Lakicevic; Ambra Gentile; Valdemar Stajer; Bojan Raskovic; Nina Vojvodic; Roberto Roklicer; Tatjana Trivic; Sergey Tabakov; Sergey Eliseev; Antonino Bianco (BMC, 2021)
Abstract Background Rapid weight loss (RWL) is commonly practiced in combat sports. Both magnitude and methods used to induce RWL are largely similar among combat sports, but currently, there is no data on RWL methodology used by sambo athletes. Therefore, the aim of this study was to determine RWL procedures sambo athletes apply to lose weight rapidly. Methods The sample consisted of 199 participants, of which 132 males and 67 females who participated in the World Sambo Championship 2020 held in Novi Sad, Serbia. Each participant received RWL questionnaire that was available in multiple languages, and every participant was instructed how to fill it out. Results Almost 87% of sambo participants declared to have intentionally cut their weight prior to the competition, whereby 5.27 kg (SD: ±7.57) was lost. Gradual dieting, sauna use and skipping meals were the most dominant methods used to reduce weight prior to competition while more extreme methods of RWL such as the use of laxatives, diuretics, diet pills and vomiting were also implemented but by much smaller fragment of the participants involved. Conclusions Findings from our study largely match with previously conducted RWL studies in terms of prevalence, magnitude and methods used by combat sport athletes, especially in judo and wrestling. Knowing the hazardous consequences of RWL, alternative methods of sustainable weight loss should be considered.